Kinerja Pendidikan Dasar Setelah Sembilan Tahun Otonomi Asimetris di Provinsi Papua Barat - Mohammad Uswanas; Yeremias T. Keban; Agus Heruanto Hadna; Pande Made Kutanegara (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2018)
Special Autonomy (Otsus) for Papua and West Papua is expected to improve people’s welfare comprehensively. The implementation of Otsus for Papua and West Papua has emphasized on the development or improvement of education, particularly basic education, particularly the basic education. The granting of Otsus status is accompanied by a sufficient financial supports to conduct development programs in both provinces. However, a question has araised which needed to be answered. Did the large financial support could significantly increase the coverage as well as improve the quality of basic education services in West Papua Province? The purpose of this study is to determine the driving and hindering factors of education performance in West Papua Province by utilizing descriptive-evaluative methods and ex-post facto. Secondary data is obtained from relevant institutions and pimary data is obtained from in-depth interviews, participatory observations, document reviews and Focus Group Discussions (FGD). The study reveals that the policy of asymmetric decentralization education in West Papua Province is far from expectations. Factors that hindered the improvement basic education in West Papua Province are policy implementations, standardization of achievements, regional sovereignity in preparing program plans and action plans. Asides from that were specific factors, such as accessibilty, school proximity, geographical constraints and low dedication of teachers.